Revisiting the twin deficits hypothesis: A quantile cointegration analysis over the period 1791-2013 - Nikolaos Antonakakis; Juncal Cu\~nado Eizaguirre; Rangan Gupta; Mawuli Segnon (Journal of Applied Economics, 2019)
We revisit the twin deficits hypothesis by examining the long-run cointegrating relationship between the US budget and trade deficits across various quantiles using a unique dataset for the period 1791-2013. The main results suggest the existence of nonlinearities and structural breaks in the relationship between the trade and budget deficits, indicating that the long-run relationship between the two variables has not been constant overtime. Furthermore, we find evidence in favour of the twin deficits hypothesis. Finally, the results suggest that the cointegrating coefficient in the long-run relationship between the two variables is not constant across different quantiles. In fact, we find that an increase in the budget deficit will have a greater effect on the trade deficit at quantiles below the median than at higher quantiles, suggesting that the effectiveness of restrictive fiscal policies directed to reduce trade deficits will depend on the actual size of the budget deficit.
Keywords: 330; non-linearities; quantile ARDL model; structural breaks; Twin deficits hypothesis